1999
DOI: 10.1152/ajpheart.1999.277.4.h1630
|View full text |Cite
|
Sign up to set email alerts
|

A13C NMR double-labeling method to quantitate local myocardial O2consumption using frozen tissue samples

Abstract: Measurement of local myocardial O(2) consumption (VO(2)) has been problematic but is needed to investigate the heterogeneity of aerobic metabolism. The goal of the present investigation was to develop a method to measure local VO(2) using small frozen myocardial samples, suitable for determining VO(2) profiles. In 26 isolated rabbit hearts, 1.5 mmol/l [2-(13)C]acetate was infused for 4 min, followed by 1.5 min of [1,2-(13)C]acetate. The left ventricular (LV) free wall was then quickly frozen. High-resolution (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 26 publications
0
27
1
Order By: Relevance
“…The infusion of unlabeled acetate was then quickly switched to [2-13 C]acetate (at unchanged concentration) for exactly 4 min, after which another quick switch was made to the infusion of [1,2-13 C]acetate for 1.5 min. The second label increases parameter estimation accuracy (41,43). After exactly 5.5 min of [ 13 C]acetate infusion, a part of ϳ2 ϫ 2 cm of the anterior left ventricular free wall, immediately adjacent to the LAD, was quickly freeze-clamped in situ inside an aluminium clamp precooled to the temperature of liquid nitrogen, cut out of the heart, and immediately placed into liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The infusion of unlabeled acetate was then quickly switched to [2-13 C]acetate (at unchanged concentration) for exactly 4 min, after which another quick switch was made to the infusion of [1,2-13 C]acetate for 1.5 min. The second label increases parameter estimation accuracy (41,43). After exactly 5.5 min of [ 13 C]acetate infusion, a part of ϳ2 ϫ 2 cm of the anterior left ventricular free wall, immediately adjacent to the LAD, was quickly freeze-clamped in situ inside an aluminium clamp precooled to the temperature of liquid nitrogen, cut out of the heart, and immediately placed into liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…The NMR multiplet peaks were analyzed with a previously published and validated computer model, schematically depicted in Fig. 2 (43). In brief, the model consists of 132 differential equations (for detailed description of the equations, see appendix to Ref.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sonntag et al (87) observed increased deoxyglucose uptake in high-flow regions. Likewise, van Beek et al (95) observed that the turnover of acetate was high in high-flow regions compared to lowflow regions; since this was the only substrate provided, they concluded that local flow must be nearly proportional to local O 2 consumption. Recently, Decking et al (31) using 13 Cpyruvate found a similar relationship.…”
Section: Substrate Uptake Ratesmentioning
confidence: 95%